Lingual Osseous Choristoma of the Tongue Base: Unusual Presentation of a Rare Entity - Matthew J. Heinz; Scott M. Peters; Salvatore M. Caruana; Angela J. Yoon (Case Reports in Otolaryngology)
Osseous lesions of the tongue, also referred to as osseous choristomas, are benign growths of bony tissue. These lesions are not true neoplasms but rather represent growth of normal tissue at an abnormal location. Clinically, they appear as exophytic masses of the tongue, and they are treated by surgical excision. Lingual osseous choristomas are rare entities, with only 71 reported cases in the literature. We present the case of a lingual osseous choristoma of the tongue base in a 21-year-old female. Of the cases of lingual osseous choristoma reported in the literature, ours is only the fifth case to involve this location.